Komparasi Tingkat Kerusakan Jalan antara Metode PCI dan Bina Marga (Studi Kasus: Jalan Raya Demak-Kudus, Gajah, Kabupaten Demak) (Indonesian Journal of Civil Engineering Study, 2025)
Roads are a vital element of infrastructure that support public mobility and drive economic growth. Road damage can disrupt traffic flow, increase vehicle maintenance costs, and potentially cause accidents. In Demak Regency, particularly on the Demak-Kudus Highway in Gajah District, road damage has become a major challenge in infrastructure maintenance.This study compares two methods of road condition assessment: the Pavement Condition Index ( (PCI)) and the Bina Marga method. PCI evaluates road conditions on a scale of 0-100, while the Bina Marga method uses the Priority Order (UP) system to determine repair needs. The research results indicate that PCI scores range from 50 (Fair) to 89 (Excellent), suggesting that most roads are still usable but require maintenance. The Bina Marga method produces an average UP score of 6.17 highlighting the need for periodic maintenance. Based on the comparison, the PCI method provides a more detailed assessment of road damage, whereas the Bina Marga method is more effective in prioritizing repairs. A combination of both methods can serve as an optimal solution for road maintenance planning.